1998
DOI: 10.1103/physrevb.58.5684
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-long-range order in random-anisotropy Heisenberg models

Abstract: Monte Carlo simulations have been used to study a discretized Heisenberg ferromagnet (FM) with random uniaxial single-site anisotropy on L × L × L simple cubic lattices, for L up to 64. The spin variable on each site is chosen from the twelve [110] directions. The random anisotropy has infinite strength and a random direction on a fraction x of the sites of the lattice, and is zero on the remaining sites. In many respects the behavior of this model is qualitatively similar to that of the corresponding random-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 47 publications
(53 reference statements)
2
30
1
Order By: Relevance
“…17 In three dimensions, instead, the phase diagram has been controversial for a long time. While for small values of D numerical simulations 5,[18][19][20][21][22] confirmed the existence of a finitetemperature transition ͑though QLRO was never observed͒, in the SRAM even the existence of the transition was in doubt. 21 In Ref.…”
Section: Introductionmentioning
confidence: 95%
“…17 In three dimensions, instead, the phase diagram has been controversial for a long time. While for small values of D numerical simulations 5,[18][19][20][21][22] confirmed the existence of a finitetemperature transition ͑though QLRO was never observed͒, in the SRAM even the existence of the transition was in doubt. 21 In Ref.…”
Section: Introductionmentioning
confidence: 95%
“…In the RAN model, Cleaver et al [49] found that the low temperature phase of the RAN model, at least for one value of D, exhibited QLRO, while Chakrabarti [58] asserted that there was a value of D below which LRO was retained. Extensive simulations [65,66] suggest that LRO is lost even at low D in the analogous magnetic models. The Larkin-Imry-Ma theory in the RAN case [49] suggests that the LRO should always be unstable at least with respect to the formation of domains, with short-range order, and this is in general what has been found in a number of studies on the SSS model [22,[61][62][63].…”
Section: Introductionmentioning
confidence: 99%
“…While an Imry-Ma-type argument 7 of model ͑1͒ leads to a conclusion that any nonzero anisotropy D destroys long-range magnetic order in three dimensions, it is predicted by field theoretical analysis 2,10,11 that the model realizes QLRO at lowtemperature and weak-anisotropy region. Numerical studies of model ͑1͒ have been restricted to approximate discretized models or small sizes, [12][13][14] and the QLRO phase was numerically confirmed in Ref. 14.…”
mentioning
confidence: 99%